Amazing wolves, dogs & foxes - Ling, Mary.; Young, Jerry (New York : Knopf, 1991)
Text and photographs introduce amazing members of the Canidae family, including the dingo, the grey wolf, and the Arctic fox.
Includes index.
Booklist.
5.5
K-3
Keywords: Foxes -- Juvenile literature; Dogs -- Juvenile literature; Wolves -- Juvenile literature; Canidae -- Juvenile literature; Wolves; Dogs; Foxes; Canidae; Foxes; Dogs; Wolves; Canidae; Wolves; Dogs; Foxes; Canidae